If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-9)-(-5+3)=1
We simplify the equation to the form, which is simple to understand
(x-9)-(-5+3)=1
Simplifying terms in parentheses
(x-9)-(-2)=1
Remove unnecessary parentheses
x-9-(-2)=1
Remove unnecessary parentheses
x-9+2=1
We move all terms containing x to the left and all other terms to the right.
+1x=+1+9-2
We simplify left and right side of the equation.
+1x=+8
We divide both sides of the equation by 1 to get x.
x=8
| 0.6(x-13)=14 | | 6x^2+7x^2-3x= | | 10+(-11)+(-12)= | | 3(44)+2r=240 | | 10+b/18=11 | | 2w+2(3w+1)=50 | | 45x+100= | | -85+5x+3x=43 | | 6(x-a)=4(x-5) | | 2[6x-7(x-1)]=5x-21 | | 9x+5y=56 | | (-x)(3y)(-2x)= | | 2x^2-27X-4565=0 | | -2x-1000= | | x+3=2(y+3) | | 2(x+4)-7=3x-5(x+1) | | 8x+30y+75x+16y+4x= | | (x+3)-2(3x-7)=5x-(x+3) | | -2x-6x-113=55 | | -4.6x=-92 | | 2x^2-2x=-1 | | 4.4x+2=3.4x | | -20=4x+3(2x-2) | | 3x+4y+10+12x+y+1= | | 1x+4y=4 | | 4=2x^3+x^2-8x | | x(1+y)=a | | 20+6x(4-2)= | | 4(x+2)=6 | | 4x+5-2x=14 | | -16f-30= | | 7x-19=6x |